Effect of delayed start of light-curing on microtensile bond strengths of two adhesives bonded to dentin - Araujo, Tabata Dutra [UNESP]; Bresciani, Eduardo [UNESP]; Gomes Torres, Carlos Rocha [UNESP]; Borges, Alessandra Buehler [UNESP]; Barcellos, Daphne Camara [UNESP]; Pucci, Cesar Rogerio [UNESP] (Elsevier B.V., 2014)
The aim of the present study was to evaluate the microtensile bond strength to dentin (ATBS) of two total-etching adhesives applied with delays of 1-30 s for curing. Fifty extracted molar teeth were used. Occlusal enamel was sectioned to expose flat dentin surface, which was further polished with 600-grit paper for smear layer standardization. The specimens were divided into two groups, G1: Single Bond total-etching adhesive (SB), and G2: Prime & Bond NT total-etching adhesive (PB). Each group was further divided into 5 subgroups according to the delayed light-cure initiation after the adhesive systems application (n=5): Subgroup 1s - 1 s; Subgroup 5s -5 s; Subgroup 10s - 10 s; Subgroup 20s - 20 s; Subgroup 30s - 30 s. Composite resin cones 5 mm height and 10 mm in diameter were fabricated. Specimens were stored in distilled water at 37 degrees C for 24 h and sectioned to obtain 1 x 1 mm(2) transversal specimens. Specimens were thermocycled and mu TBS was measured. Data were submitted to two-way ANOVA (AdhesiveXDelay time) and Tukey's test. The level of significance was set at 5%. The results in mean MPa(+/- SD) for interaction between adhesive and delay time were: PB/1s - 23.82 +/- 2.54a; SB/5s - 19.52 +/- 2.67b; PB/5s - 18.56 +/- 3.06bc; SB/1s - 15.49 +/- 2.69cd; SB/20s - 16.33 +/- 2.55d; SB/10s - 13.88 +/- 1.67d; PB/10s - 11.04 +/- 1.28e; PB/30s - 10.89 +/- 1.31e; PB/20s - 10.24 +/- 2.33e; SB/30s - 9.19 +/- 1.91e. It was concluded that light-cure initiation timing of total-etching adhesives interferes negatively with mu TBS to dentin. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Dental bonding; Tensile strength; Dentin